The ability to assess the situation and its relationship to the skills of setting and spiking in volleyball for students - Hafez, Prof.Dr.Hatem Faleh (Sulaimani Journal for Humanities, 2026)
The importance of this research lies in studying the correlation and relationship between situational assessment ability and the skills of setting and spiking in volleyball. The research problem stems from a decline in performance levels in both setting and spiking skills. This is the core of the problem. The study aimed to identify the relationship between situational assessment ability and volleyball setting skills among students, as well as the relationship between situational assessment ability and spiking skills. The researcher hypothesized a significant correlation between situational assessment ability and volleyball setting skills, and a significant correlation between situational assessment ability and spiking skills. The researcher used a descriptive approach with correlational analysis, as it was suitable for the nature of the research problem and its objectives. The research population consisted of third-year students at the College of Physical Education and Sports Sciences, University of Kufa, totaling 68 students. A simple random sample of 34 students (Section B) was selected, in addition to a pilot sample of 4 students. The researcher conducted tests to assess situational assessment ability and skill performance. For the volleyball setting and spiking skills of the research group A, in the college volleyball hall, after completing the tests and using appropriate statistical analyses, the results were presented and analyzed, leading to the following conclusions: The results showed a significant correlation between the ability to change position and the skill performance in setting. The student possesses coordination and accuracy in setting. - There is a proven correlation between the ability to change position and the accuracy of the volleyball spik. The following recommendations were made: 1- Emphasize other elements of physical fitness, namely strength, flexibility, agility, and coordination, due to their impact on developing the skill performance of both skills. 2- Emphasize accuracy and positional assessment exercises using assistive devices for performing the relevant tests, and emphasize the use of accuracy in conjunction with other elements of physical fitness to gain motor experience.
Keywords: The ability to assess; the situation; the skill of preparation; the skill of crushing the attack